Internal audit function, political characteristics, and compliance with government accrual-based accounting standards in Indonesian local government - Sutaryo, Sutaryo; Salawati, Sahari; Shaharudin, Jakpar; Sophee Sulong, Balia (Universidad Nacional Autónoma de México, 2023)
We investigate the effect of local government internal audit function and political characteristics on accounting compliance based on government accrual-based accounting standards in Indonesia while controlling for financial and local government characteristics. Our analysis is conducted for 2015-2018 with panel data regression, equipped with a robustness test using logistic regression. Our results show that internal audit function capability, maturity, expertise, and size play a role in improving accrual-based accounting compliance and find positive effects of legislative coalition, gender, and size. The robustness test shows that the effects remain consistent for most variables. This study implications local governments in Indonesia and the Financial and Development Supervisory Agency to improve local government internal audit function capability, maturity, and human resource availability through various supporting policies. This study contributes to the literature as one of the earliest comprehensive studies that examine internal audit function and political characteristics in all Indonesian local governments.